VD_FINDINFO HC / 2025 / 223 vom 5. Mai 2025 - VD Tribunal cantonal (2025)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, CRÉANCE, PREUVE FACILITÉE, REJET DE LA DEMANDE | 837 al. 1 ch. 3 CC, 839 CC, 961 al. 3 CC